Rural land management and flood risk management: stakeholder and policy analysis - Posthumus, Helena; Morris, Joe (Cranfield University, 2006)
Climate change, perceived increase in flood incidence and changing priorities in the countryside have led to a growing concern that changes in land use in rural areas have increased the exposure of urban settlements to flood risk, not only at a local level but also at the catchment scale. This has led to calls for interventions to reduce the potential runoff from farmland and in some cases to reduce the degree of protection afforded to farmland in order to provide temporary storage of flood waters. It is also claimed that reducing runoff from farmland could reduce diffuse pollution from agriculture. Furthermore, the creation of flood storage areas could provide opportunities for wetland creation and enhanced biodiversity.
The work was part of Work Package 7.2 on Policy and Stakeholders in Rural Areas, conducted during 2005/06 by Cranfield University as part of the Flood Risk Management Research Consortium (FRMRC).